Review on the pathogenesis and epidemiology of oral cancer induced by Areca catechu L. - Zhao Zhenyu; Su Xiaojing; Zheng Yu; Li Jia; He Xiaoning; Hou Jianhua (生物医学转化, 2025)
Areca catechu L., a traditional masticatory widely consumed in Asia, has been classified as a Group 1 carcinogen by the International Agency for Research on Cancer (IARC) of the World Health Organization due to its confirmed association with oral and oropharyngeal cancers. This study systematically elucidates the mechanistic roles of areca nut components and their metabolites in oral carcinogenesis, with a focus on four pivotal pathological processes: arecoline-induced aberrant cell signaling pathways, DNA alkylation by nitrosamine derivatives, oxidative stress-induced genomic instability, and pro-tumorigenic microenvironment remodeling. By integrating global epidemiological data with regional exposure differences, a dose-response relationship was revealed between long-term betel quid chewing and the development of oral squamous cell carcinoma (OSCC) and precancerous lesions such as oral submucous fibrosis (OSMF). Strengthening interdisciplinary integration is needed to elucidate the dynamic process of Areca catechu L.-induced oral carcinogenesis and to develop region-specific prevention and control strategies, providing a scientific basis for reducing the burden of related diseases.